The Impact of Ethnicity on Objectively Measured Physical Activity in Children. (2nd January 2013) - Eyre, Emma Lisa Jane; Duncan, Michael J.
Abstract : Obesity and obesity-related diseases (cardiovascular disease/metabolic risk factors) are experienced differently in individuals from different ethnic backgrounds, which originate in childhood. Physical activity is a modifiable risk factor for obesity and related diseases. Both physical activity and metabolic risk factors track to adulthood, and thus understanding the physical activity patterns in children from different ethnic backgrounds is important. Given the limitations of self-report measures in children, this study provides a review of studies which have objectively measured physical activity patterns in children from different ethnic backgrounds. From a total of 16 studies, it can be concluded that physical activity does seem to vary amongst the ethnic groups especially South Asian and Black compared to White EU (European Union). The findings are less consistent for Hispanic/Mexican American children. However, there are several methodological limitations which need to be considered in future studies. Firstly, there is a need for consistency in the measurement of physical activity. Secondly, there are a range of complex factors such as socioeconomic status and body composition which affect both physical activity and ethnicity. Studies have failed to account for these differences limiting the ability to generalise that ethnicity is an independent risk factor for physical activity.